2016
DOI: 10.3389/fneur.2015.00269
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Aging Vestibular Function

Abstract: Much is known about age-related anatomical changes in the vestibular system. Knowledge regarding how vestibular anatomical changes impact behavior for older adults continues to grow, in line with advancements in diagnostic testing. However, despite advancements in clinical diagnostics, much remains unknown about the functional impact that an aging vestibular system has on daily life activities such as standing and walking. Modern diagnostic tests are very good at characterizing neural activity of the isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 126 publications
2
65
0
Order By: Relevance
“…Such deficits can be further enhanced by altered eye movement behavior (Dowiasch et al, 2015), which changes the way older adults sample the outside world. Secondly, epidemiological, physiological and histopathological studies have shown that vestibular function declines with age (Anson and Jeka, 2015). While the vestibular system is known for its role in maintaining balance and postural control, increasing evidence demonstrates important connections between the vestibular system and spatial navigation in humans (Brandt et al, 2005) as previously reported in rodents (Potegal et al, 1977).…”
Section: How Does Aging Affect Our Ability To Compute Online Spatimentioning
confidence: 99%
“…Such deficits can be further enhanced by altered eye movement behavior (Dowiasch et al, 2015), which changes the way older adults sample the outside world. Secondly, epidemiological, physiological and histopathological studies have shown that vestibular function declines with age (Anson and Jeka, 2015). While the vestibular system is known for its role in maintaining balance and postural control, increasing evidence demonstrates important connections between the vestibular system and spatial navigation in humans (Brandt et al, 2005) as previously reported in rodents (Potegal et al, 1977).…”
Section: How Does Aging Affect Our Ability To Compute Online Spatimentioning
confidence: 99%
“…The rest of the sensory systems (Table ) also undergo a series of changes that have a negative impact on one's quality of life and well‐being, but they have not been studied extensively. The vestibular system, which is responsible for balance maintenance (i.e., by perceiving changes in direction and motion and by adjusting the activity of the postural muscles) and for gaze and head stabilization, undergoes significant changes that mainly affect the hair cells in the semicircular canals, the maculae of the saccule and the utricle, the central vestibular structures, the primary and secondary vestibular neurons, as well as the vestibulo‐spinal and ocular functions which, in turn, influence balance and gait stabilization during repetitive behaviors (e.g., walking) . Recent evidence also demonstrates age‐related decreases in functional connectivity and increased variability for the processing of vestibular information that is mediated by a multisensory vestibular network (i.e., superior, middle, and inferior frontal and temporal gyri; lingual gyrus; insula; superior and inferior parietal lobe parietal operculum; posterior cingulate gyrus cuneus; thalamus; and cerebellar tonsil) .…”
Section: Sensory Processing Alterations In Old Agementioning
confidence: 99%
“…Given that evidence from animal studies indicates that ageing leads to a degeneration of the stria vascularis in the inner ear (Schmiedt, 2010), it appears possible that this physiological change could lead to concomitant impairment in hearing and mobility (Agrawal et al, 2009;Anson & Jeka, 2016;Zuniga et al, 2012).…”
Section: Mobility (D4) -Walking (D450)mentioning
confidence: 99%